The Effect of Income Tax on Economic Growth in Indonesia - Hilda Hidayah; Dewi Anggraini Lestari; Nurul Hidayah; Reni Eriska Ritonga; Mhd. Faakhir Irwan Ritonga (ISNU Sumatera Utara, 2025)
This study aims to analyze the influence of Income Tax on economic growth in Indonesia. Income Tax is one of the main sources of state revenue used to finance development and improve people's welfare. The study uses secondary data from various official sources and applies quantitative methods to measure the relationship between Income Tax revenues and national economic growth. The results of the study show that tax revenues, including Income Tax, generally have a positive and significant effect on economic growth at the provincial and national levels, especially in the long term, as tax funds are used to fund productive projects and infrastructure development that boost economic activity. However, there are also findings that in the short term the influence of Income Tax on economic growth is not always significant, depending on other macroeconomic factors. The implications of this study confirm the importance of efficient tax management and the expansion of the tax base to support sustainable economic growth. The government also needs to ensure that tax policies do not hinder investment and continue to encourage public participation in national economic development.